2016
DOI: 10.3748/wjg.v22.i42.9427
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection is not associated with disease progression of chronic hepatitis C virus infection

Abstract: AIMTo clarify the prevalence of occult hepatitis B virus (HBV) infection (OBI) and the association between OBI and liver disease progression, defined as development of liver cirrhosis or hepatocellular carcinoma (HCC), worsening of Child-Pugh class, or mortality in cases of chronic hepatitis C virus (HCV) infection.METHODSThis prospective cohort study enrolled 174 patients with chronic HCV infection (chronic hepatitis, n = 83; cirrhosis, n = 47; HCC, n = 44), and evaluated disease progression during a mean fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We previously reported on occult HBV infection in HCV patients 25 . According to one report, occult HBV infection is not associated with disease progression in patients with chronic HCV infection 26 . HBV co-infection reportedly can also cause HCC.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported on occult HBV infection in HCV patients 25 . According to one report, occult HBV infection is not associated with disease progression in patients with chronic HCV infection 26 . HBV co-infection reportedly can also cause HCC.…”
Section: Discussionmentioning
confidence: 99%
“…High prevalence rates of OBI are observed among patients with hepatitis C (HCV, 1%-20%) (Almeida et al, 2019;Cho et al, 2016;Mandour et al, 2015;Yamaji et al, 2018), patients with HIV (10%-40%) and patients with HCC (>40%) (Ndjoyi-Mbiguino et al, 2018;Dinesha et al, 2018;Saha et al, 2017). The relatively high prevalence reported in HCV or HIV-infected populations and HCC patients might be due to the fact that clinic triggered more frequent investigations in these populations.…”
Section: Prevalence Of Obi In the Worldmentioning
confidence: 99%
“…In some studies, the absence of an interaction between OBI and chronic hepatitis C was observed, 45,46 while others have identified that some mutations in HBV may favor its occult phenotype in chronic HCV carriers. 47 OBI has been suggested to be associated with hepatocarcinogen-…”
Section: Discussionmentioning
confidence: 99%